The Effect of Varied Time Interval and Micro-Current (Direct) on the Level of Biomarker (IL-6) and Rate of Tooth Movement: An Animal Study - Parnita Dwivedi; Ashish Agrawal; Subash Chandra Gupta; Tehmin Chou (Indian Journal of Dental Research)
Introduction: Exogenous application of direct current (DC) on piezoelectric biopolymers results in biochemical modifications in the intracellular/extracellular regions which profoundly affects the pace of bone turnover. A qualitative examination of DC (waveform and frequency) provides ideal qualities of current. Material and Method: 20 female Wistar rats (Rattus norvegicus) were randomly selected and divided into control (group 1–4 rats) with orthodontic appliance (OA) and experimental groups (OA + Micro-current (MC). Experimental groups were subdivided into four groups (group 2–20 μA/5 sec, 3-20 μA/10 sec, 4-15 μA/5 sec, 5-15 μA/10 sec with four rats in each). The tooth movement was recorded every 24th hours for 7 days. Gingival crevicular fluid (GCF) was collected 6 hr, 12 hr, 24 hr, 3rd day and 168 hrs with the absorbent paper points at specific location around the tooth in control and experiment groups. Histopathological analysis was done on 168 hrs to assess the osteoclastic activity around the root. Interleukin-6 (IL-6) concentration was accessed using enzyme-linked immunosorbent assay (ELISA). The data were subjected to one-way ANOVA and Tukey’s post hoc test. Results: There was a statistically significant difference in tooth movement, group 3 (20 μA/10 sec) showed an increased rate of tooth movement on the 168 hrs. The level of IL-6 was maximum on 72 hrs in experimental group 3. Conclusion: The study showed time interval/frequency, the waveform, and the amount of current play a significant role in determining bone turnover and rate of tooth movement.